THERMAL CONDITION ANALYSIS FOR RAMP DEVELOPMENT IN CUT AND FILL MINE PT XYZ USING COMPUTATION FLUID DYNAMICS - Arya Rhaditya Pongtiku, Lachlan
Thermal conditions are one of the significant factors that greatly influence the efficiency of mining activities, as uncomfortable thermal conditions can disrupt activity performance. Therefore, an analysis of the thermal conditions of a work area is necessary, in this case, the ramp development, to achieve the desired effective temperature. The study utilizes simulation through a numerical method based on computational fluid dynamics using ANSYS Fluent R1 2023 software. Changes in conditions due to heat sources will be carried out using heavy equipment such as a 120 kW LHD machine, a 120 kW mine truck, and a 44 kW jumbo drill. Planes will be created to represent the resulting areas. Based on the modeling results, it was found that during mucking, hauling, and drilling activities, there is an increase in temperature due to the presence of heavy equipment operations. When mucking is performed by the Load-Haul-Dump (LHD) machine during loading activities in the front development, the temperature increase ranges from 2.5 to 3.5°C. Subsequently, there is a temperature rise on Plane 5 to 8, which are passed through by the LHD, resulting in temperature increases of 0.8°C to 1.9°C respectively. During hauling and drilling activities, there is a temperature gradient increase due to the stationary LHD, resulting in temperature rises of 0.12°C per hour for Plane 5 and 0.1°C for Plane 6 to 8. The presence of the jumbo drill causes a temperature increase with a gradient of 0.75°C per hour for 2 hours of activity, followed by a decrease of 1°C after the activity ceases. The movement of the mine truck also causes temperature increases on Plane 2 to 8, with increases of 0.45°C to 2.2°C. The results of this ANSYS modelling are still in terms of dry bulb temperature. The tunnel model that was analyzed still meets the feasibility standards based on regulations regarding ventilation systems in Indonesia, with a maximum effective normal temperature of 23.6°C